Knowing, Being, and Doing: Aboriginal and Non-Aboriginal Collaboration in Cancer Services. (July 2017) - Zubrzycki, Joanna; Shipp, Rick; Jones, Victoria
This qualitative inquiry explored the processes and practices of collaboration as experienced by a group of Australian multidisciplinary Aboriginal and non-Aboriginal health workers. Each worker had participated, for a period of 2 to 5 years, in an Australian Government–funded project in which a range of health initiatives led to improved access to cancer services by Aboriginal communities in a rural region of South Eastern Australia. Initiatives which addressed high rates of mortality from cancer, poor access to cancer screening, and engagement with cancer treatment were developed through the formation of close working relationships between Aboriginal and non-Aboriginal health workers. These relationships were regarded as personally and professionally transformative. Through the sharing of knowledge, skills, and experiences, new ways of knowing, being, and doing emerged. Developing a deeper understanding of cross-cultural collaboration is one way of addressing complex health problems and building the capacity of the health workforce.